ISOLASI DAN KARAKTERISASI BAKTERI PENGHASIL BIOGUM XANTHAN DARI BRASSICA OLERACEAE ASAL KEPUNAN MAGELANG JAWA TENGAH - Mustini Mustini; Erny Qurotul Ainy (Kaunia: Integration and Interconnection Islam and Science, 2014)
Food additive such as gelling agent and emulsifier is essential ingredient in food processing. Microbial gum such as xanthan gum is a hydrocolloid microbial that could play as gelling agents and emulsifier in food industry. Xanthan gum is produced by a phytopathogenic bacteria, Xanthomonas campestris. This study aims to isolate xanthan gum producing local bacteria of Brassica oleracea L. leaf showing black root symptom. The isolation performed by inoculating leaf an nutrient agar media. Three isolated bacteria were purified and tested their ability in producing gum using YDC broth for 4 days. The test result showed that the isolates were Xh.A, Xh.B, and Xh.C had ability to produce biogum. Profile matching resul t showed   that Xh.A, Xh.b, and Xh.C   were identified as member of Pseudomonas, Aureobacterium and Xanthomonas genus, respectively.